Expanding marketing empirical generalisations to health behaviours: Physical activity is not so different from buying behaviour, after-all. Issue 4 (November 2017) - Wilson, Amy L.; Sharp, Byron; Nguyen, Cathy; Bogomolova, Svetlana
Highlights: Physical activity is a continuum - it is not a binary 'on' or 'off' type behaviour. Within one week most people are non- or light-engagers of various physical activities. Less rational drivers of physical activity need greater consideration over more rational factors. Promotion needs broad reach and consistency over time to build mental availability. Small changes are be detected with continuous variables and longer time periods of analysis. Abstract: The Negative Binomial Distribution (NBD) is a model that describes consumer purchase frequency over time. This paper tests the applicability of this model to a novel context: physical activity behaviours (using data obtained from Australia, the United States, and Singapore). The fit of the NBD to the data demonstrates that physical activity behaviour is consistent with other consumer behaviour patterns. Within a one-week period, the majority of people are either non- or light-engagers of the different intensities of leisure-time physical activity. Yet, people are not 'active' or 'inactive', rather, degree of engagement varies. Infrequency of reported levels and variety of physical activities might be due to health promotion having a strong focus on rational persuasion and less focus on mass communication that builds mental availability. Our contribution broadens the applicability of the NBD showing it can be helpful for those seeking to promote health behaviours, not just purchases. Chinese Abstract: 负二项分布（NBD）是描述消费者在一定时期内的购买频率的模型。本文测试了该模型在一个新的背景下的适用性：身体活动行为（使用从澳大利亚、美国和新加坡获得的数据）。NBD对数据的拟合性表明，身体活动行为与其他消费者行为模式一致。在一个星期的时间里，大多数人对于不同等级的休闲体育活动，不是轻度参与，就是不参与。然而，并不能把人们分成"活跃"或"不活跃"，与此相对，是参与的程度各不相同。报告中对于各级别和类型的体育活动的低频率参与，可能源于健康宣传时通常重点在于理性说服，而较少注重能够建立心智显著性的大众传播。本文拓展了NBD的适用范围，表明它可以帮助推动健康行为，而不仅仅是购买。